Catalyst-assisted electrochemical deposition of graphene decorated polypyrrole nanoparticles film for high-performance supercapacitor - Lim, Yee Seng; Lim, Hong Ngee; Lim, Su Pei; Huang, Nay Ming (Royal Society of Chemistry, 2014)
A simple catalyst-assisted electrochemical deposition technique has been implemented to control the particle size of polypyrrole in the range of 5 to 10 nm embedded on graphene sheets, in which the nanocomposite will be used as a supercapacitor electrode material. The polypyrrole/graphene nanocomposite resulting from this approach maximizes the pseudocapacitive contribution of redox-active polypyrrole and electrical double layer capacitance (EDLC) contributed by individual graphene sheets. Specific capacitance, as high as 797.6 F g−1 is obtained when 1.0 mM of FeCl3 catalyst is added to the deposition solution, which is approximately four times higher than that of polypyrrole film and 2.6 times higher than that of polypyrrole/graphene nanocomposite in the absence of catalyst. This increase is attributed to the controlled particle size of polypyrrole growth on individual graphene sheets, which prevents the overlapping of graphene sheets. This gives rise to a highly open structure, which provides an easier access of electrolyte within the matrix of the nanocomposite film. A fabricated symmetric supercapacitor device yields a specific capacitance of 463.15 F g−1 and capacitance retention of 77.7% over 10 000 charge/discharge cycles at a current density of 1 A g−1. The nanocomposite serves as a promising electrode material for supercapacitors.